Mitochondrial–Lysosomal Axis in Acetaminophen Hepatotoxicity - Moles, Anna; Torres, Sandra; Baulies, Anna; Garcia-Ruiz, Carmen; Fernandez-Checa, Jose C. (Frontiers in Pharmacology, 2018)
Acetaminophen (APAP) toxicity is the most common cause of acute liver failure and a major indication for liver transplantion in the United States and Europe. Although significant progress has been made in understanding the molecular mechanisms underlying APAP hepatotoxicity, there is still an urgent need to find novel and effective therapies against APAP-induced acute liver failure. Hepatic APAP metabolism results in the production of the reactive metabolite N-acetyl-p-benzoquinone imine (NAPQ1), which under physiological conditions is cleared by its conjugation with GSH to prevent its targeting to mitochondria. APAP overdose or GSH limitation leads to mitochondrial NAPQ1-protein adducts formation, resulting in oxidative stress, mitochondrial dysfunction and necrotic cell death. As mitochondria are a major target of APAP hepatotoxicity, mitochondrial quality control and clearance of dysfunctional mitochondria through mitophagy emerges as an important strategy to limit oxidative stress and the engagement of molecular events leading to cell death. Recent evidence has indicated a lysosomal-mitochondrial cross-talk in the promotion of APAP hepatotoxicity. Moreover, as lysosomal function is essential for mitophagy, impairment in the fusion of lysosomes with autophagosomes-containing mitochondria may compromise the clearance of dysfunctional mitochondria, resulting in exacerbated APAP hepatotoxicity. This review centers on the role of mitochondria in APAP hepatotoxicity and how the mitochondrial/lysosomal axis can influence APAP-induced liver failure.